ANTI-DIARRHOEAL POTENTIAL OF ERYTHRINA INDICA LAM-LEAF EXTRACTS IN LABORATORY ANIMALS (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Erythrina indica Lam leaf has been used traditionally in ayurveda for the treatment of diarrhoea and dysentery. However, the claims of ayurveda need to be validated by a suitable experimental model. Therefore, the present study was undertaken to evaluate the effect of ethanol and aqueous extracts of Erythrina indica leaf for its anti-diarrhoeal potential against several experimental models of diarrhoea in albino Wistar rats. The anti-diarrhoeal activity of ethanol and aqueous extracts of Erythrina indica lam leaf at 500 mg/kg dose level was evaluated using castor oil-induced diarrhoea model in rats. Further, we evaluated the effect of ethanol and aqueous extracts on gastrointestinal tract motility after charcoal meal administration and PGE2 induced intestinal fluid accumulation (Enteropooling) showed significant inhibitor activity. Loperamide was used as positive control. The results point out the possible anti-diarrhoeal effect of the leaf extracts and substantiate the use of this herbal remedy as a non-specific treatment for diarrhoea in folk medicine.